The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3126/jnps.v35i1.12093
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Sleep in Infants and Toddlers Visiting at a Teaching Hospital in Lalitpur

Abstract: Introduction: Sleep is an integral part in a child's health and development. During different stages of development, there are aberrations in normal physiology of sleep which make children more susceptible to various types of sleep problems. This study was conducted to identify sleep pattern and sleep problems in Nepalese children using Nepali translation of Brief Infant Sleep Questionnaire (BISQ) screening tool. Materials and Methods: This was a descriptive cross-sectional study. Data were collected from pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
5
3
1
Order By: Relevance
“…16,17 However, in our school children, only in 2% which is much lower than that reported from China where 9.8% school children had frequent night awakenings. 18 This again could be due to dietary factors and environmental conditions like temperature which have a direct or indirect effect on sleep habits.…”
Section: Discussioncontrasting
confidence: 42%
“…16,17 However, in our school children, only in 2% which is much lower than that reported from China where 9.8% school children had frequent night awakenings. 18 This again could be due to dietary factors and environmental conditions like temperature which have a direct or indirect effect on sleep habits.…”
Section: Discussioncontrasting
confidence: 42%
“…Overall, 19.6% of the children had sleep problems in our study as per the BISQ parameter for sleep problems which is similar (20.3%) to the study findings of another study carried out in Lalitpur, Nepal [ 11 ]. However, only 5.6% of the respondents perceived that their children have sleep problems.…”
Section: Discussionsupporting
confidence: 87%
“…Though supine sleep position is generally recommended for infants to prevent the risk of sudden infant death syndrome (SIDS) [ 18 ], in our study, the most common sleeping position was found to be lateral. The lateral sleeping position has been reported to be the most common one in another study done in Nepal [ 11 ]. Most of the children in our study coslept with their parents, and research study suggest that there is no proven position for a child to sleep on in relation to their parents to prevent SIDS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations